2017
DOI: 10.1038/cddis.2017.380
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S facilitating ubiquitin aggregates clearance via autophagy attenuates type 2 diabetes-induced cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a serious complication of diabetes. Hydrogen sulphide (H2S), a newly found gaseous signalling molecule, has an important role in many regulatory functions. The purpose of this study is to investigate the effects of exogenous H2S on autophagy and its possible mechanism in DCM induced by type II diabetes (T2DCM). In this study, we found that sodium hydrosulphide (NaHS) attenuated the augment in left ventricular (LV) mass and increased LV volume, decreased reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Hydrogen sulfide (H2S), the third identified gasotransmitter after nitric oxide and carbon monoxide, is involved in a wide range of physiological and pathological processes. Our previous study suggested that H2S inhibits the ubiquitylation of superoxide dismutase (SOD) to promote the initiation of autophagy in diabetic cardiomyopathy [14]. Ji et al demonstrated that H2S regulates Krüppel-like factor 5 (KLF5) transcriptional activity via specific protein S-sulfhydration to prevent myocardial hypertrophy [15].…”
mentioning
confidence: 99%
“…Hydrogen sulfide (H2S), the third identified gasotransmitter after nitric oxide and carbon monoxide, is involved in a wide range of physiological and pathological processes. Our previous study suggested that H2S inhibits the ubiquitylation of superoxide dismutase (SOD) to promote the initiation of autophagy in diabetic cardiomyopathy [14]. Ji et al demonstrated that H2S regulates Krüppel-like factor 5 (KLF5) transcriptional activity via specific protein S-sulfhydration to prevent myocardial hypertrophy [15].…”
mentioning
confidence: 99%
“…Our previous study showed that exogenous H 2 S could facilitate the clearance of ubiquitin aggregates by promoting autophagy, which contributed to its antioxidative effects in DCM (J. Wu et al, 2017). Nevertheless, the pathogenesis of DCM is complex, and the precise mechanism by which H 2 S may protect against DCM has not been thoroughly elucidated (Popov, 2013).…”
mentioning
confidence: 99%
“…[ 43 44 ] However, other research teams reported that H 2 S could protect myocardiocytes by promoting autophagy in a type 2 diabetes model. [ 45 46 ] Thus, how H 2 S exerts its protective effects on cardiomyocytes through autophagy merits further studies. We reviewed various studies investigating the regulation of autophagy by H 2 S in cardiovascular diseases to shed new light on the mechanisms for the cardioprotective role of H 2 S.…”
Section: H Ydrogen S Ulfide a mentioning
confidence: 99%